2006
DOI: 10.1021/np060252z
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrozingerone, Chalcone, and Isoeugenol Analogues as in Vitro Anticancer Agents

Abstract: Twenty-eight compounds related to dehydrozingerone (1), isoeugenol (3), and 2-hydroxychalcone (4) were synthesized and evaluated in vitro against human tumor cell replication. Except for isoeugenol analogs 27−35, most compounds exhibited moderate or strong cytotoxic activity against KB, KB-VCR (a multi-drug resistant derivative), and A549 cell lines. In particular, chalcone 15 showed significant cytotoxic activity against the A549 cell line with an IC 50 value of 0.6 μg/mL. Furthermore, dehydrozingerone analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…The positive control doxorubicin had an IC 50 value of 0.1 µg/ml. The chalcones 57b and 57c showed significant cytotoxic activity against nasopharyngeal carcinoma KB (IC 50 = 1.0 and 1.0 µg/ml) and multidrug-resistant expressing P-gp KB-VCR cell lines (IC 50 = 2.0 and 2.0 µg/ml) suggesting they are not substrates for the P-gp drug efflux pump [76].…”
Section: Adenosine Triphosphate (Atp)-binding Cassette Transportersmentioning
confidence: 99%
“…The positive control doxorubicin had an IC 50 value of 0.1 µg/ml. The chalcones 57b and 57c showed significant cytotoxic activity against nasopharyngeal carcinoma KB (IC 50 = 1.0 and 1.0 µg/ml) and multidrug-resistant expressing P-gp KB-VCR cell lines (IC 50 = 2.0 and 2.0 µg/ml) suggesting they are not substrates for the P-gp drug efflux pump [76].…”
Section: Adenosine Triphosphate (Atp)-binding Cassette Transportersmentioning
confidence: 99%
“…Elution with n-hexane afforded two compounds. Identification of these major compounds was carried out by comparing their 1 H NMR spectra with those reported in the literature (Patra & Mitra, 1981;Tatsuzaki et al, 2006) and also by GC-MS. On the basis of these results, the H. elymaitica's oil could be considered a potential natural source of trans-asarone. Asarones have also shown antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a 4-OH group, and an α, β-unsaturated double bond are essential features for the cytotoxic activity of this class of compound (Cai, Sun, X., Luo & Corke, 2006). In a report on structure activity relationships of chalcones, a series of O-methylated chalcones showed activity against human tumor cell replication (KB, KB-VCR and A 549 cell lines) (Tatsuzaki, Bastow, Nakagawa-Goto, Nakamura, Itokawa & Lee, 2006). Another investigation showed that several ring-A methoxylated chalcones exhibited cytotoxic activity by inhibiting tubulin polymerization against a variety of tumor cell lines in the low micromolar range (IC 50 < 50 μM) (Go, Wu & Liu, 2005).…”
Section: Resultsmentioning
confidence: 99%